2013
DOI: 10.1111/jocn.12251
|View full text |Cite
|
Sign up to set email alerts
|

Social support, coping strategies and health‐related quality of life among primary caregivers of stroke survivors in China

Abstract: Community healthcare providers may need to help caregivers strengthen strategies that are effective (planning, active coping, seeking instrumental and emotional support) and change those that are not helpful (venting, denial and self-blame).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
84
2
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(113 citation statements)
references
References 47 publications
16
84
2
11
Order By: Relevance
“…Many of the nursing reserches in this area have explored those caregivers who were better able to cope with stressors and had perceived fewer burdens. [23,24] In the same line of this explanation Damrosch & Pert(2007) [25] reported that in Turkey about self-reported adjustment, chronic sorrow, and coping of parents of children with chronic illness. Also, Blount et al (2008) [26] who studied evidence -based intervention of coping and stress in pediatric psychology in University of Wales, Cardiff, they have referred to the importance of coping strategies in reducing stress for parents or caregivers.…”
Section: Discussionsupporting
confidence: 51%
“…Many of the nursing reserches in this area have explored those caregivers who were better able to cope with stressors and had perceived fewer burdens. [23,24] In the same line of this explanation Damrosch & Pert(2007) [25] reported that in Turkey about self-reported adjustment, chronic sorrow, and coping of parents of children with chronic illness. Also, Blount et al (2008) [26] who studied evidence -based intervention of coping and stress in pediatric psychology in University of Wales, Cardiff, they have referred to the importance of coping strategies in reducing stress for parents or caregivers.…”
Section: Discussionsupporting
confidence: 51%
“…Skills training to offer support and teach effective coping skills, such as relaxation techniques and problem-solving techniques, are useful in lessening negative caregiver outcomes. 6,11,15,16 Empirical data that support these skills can be taught by nurses via the telephone, in conjunction with written materials. 17 Counseling to address caregivers' feelings and strategies to address their own personal care needs is also useful.…”
Section: Common Caregiver Issues and Nursing Interventionsmentioning
confidence: 99%
“…Both conditions are associated with the reduction of negative effects from exposition to physical or emotional trauma (Lawrence & Fauerbach, 2003), with the increase of quality of life of both, patients and caregivers (Yu, Hu, Efird, McCoy, 2013), and with coping with difficulties of acute burn injuries (Farrell, Bennett, & Gamelli, 2010).…”
Section: Introductionmentioning
confidence: 99%